2011
DOI: 10.1111/j.1365-2036.2011.04745.x
|View full text |Cite
|
Sign up to set email alerts
|

Randomised clinical trial: anti-viral activity of ANA773, an oral inducer of endogenous interferons acting via TLR7, in chronic HCV

Abstract: SUMMARY BackgroundThe ANA773 is an oral prodrug of a small-molecule toll-like receptor (TLR)7 agonist. Preclinical and healthy volunteer clinical studies with ANA773 have demonstrated induction of endogenous interferon-a (IFN-a) of multiple subtypes, which supports the potential utility in the treatment of chronic hepatitis C virus (HCV) infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 14 publications
1
39
0
1
Order By: Relevance
“…The drug was generally well tolerated and most of the reported adverse events symptoms disappeared rapidly during continued dosing, resulting in no dose reductions or discontinuations. Thus, ANA773 is the first oral TLR7 agonist to induce a dose-related antiviral response leading to a significant decrease in serum HCV RNA levels without the concurrent induction of prohibitive systemic side effects [55]. Hence, it is plausible that viral eradication may be enhanced using a strategy that optimally targets the host innate immune system by using an oral selective TLR7 agonist to induce a direct antiviral effect (type I interferon signature) and an indirect effect (enhancing HCV-specific immunity by cross-linking innate and adaptive immune system), resulting in rapid eradication of HCV without a myriad of adverse events.…”
Section: Reviewmentioning
confidence: 99%
“…The drug was generally well tolerated and most of the reported adverse events symptoms disappeared rapidly during continued dosing, resulting in no dose reductions or discontinuations. Thus, ANA773 is the first oral TLR7 agonist to induce a dose-related antiviral response leading to a significant decrease in serum HCV RNA levels without the concurrent induction of prohibitive systemic side effects [55]. Hence, it is plausible that viral eradication may be enhanced using a strategy that optimally targets the host innate immune system by using an oral selective TLR7 agonist to induce a direct antiviral effect (type I interferon signature) and an indirect effect (enhancing HCV-specific immunity by cross-linking innate and adaptive immune system), resulting in rapid eradication of HCV without a myriad of adverse events.…”
Section: Reviewmentioning
confidence: 99%
“…In a previous study, oral administration of the TLR7 agonist, SM‐360320 was found to generate potent antitumor immune responses in carcinoembryonic antigen transgenic mice bearing MC38 colon adenocarcinoma cells 33. In addition, oral administration of TLR7 agonists have been tested clinically (using the prodrug TLR7 agonist ANA773) and preclinically for the treatment of hepatitis C virus infection 34, 35. In the present study we compared IT and PO administration of SM‐276001 in the HM‐1 model of metastatic ovarian cancer.…”
Section: Discussionmentioning
confidence: 99%
“…A subsequent oral prodrug of isatoribine, ANA773, showed efficient induction of type I IFN and proved to be safe and well tolerated in preclinical studies. In a double-blind, placebo-controlled study of patients infected chronically with HCV, ANA773 showed a dose-dependent increase in IFN responses and a decrease in serum HCV RNA [147]. Repeated administration of ANA773 to chronic HCV patients resulted in a transient reduction in blood myeloid DC and pDC numbers and increased serum levels of IFN-α and IP-10 only in patients, who showed reduced serum HCV RNA upon drug treatment [148].…”
Section: Tlr7/8mentioning
confidence: 99%